Penulisan Naskah Film Dokumenter “Pedal Waktu Jalanan Bandung” dengan Penerapan Narasi Ekspositoris - Maitsa Alifia Salsabila; Trie Damayanti; Toto Sugito (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The documentary film “Pedal Waktu Jalanan Bandung” was a final project that explored a vintage bicycle community known as Paguyuban Sapedah Baheula Bandoeng (PSBB). The creation of this work is driven by a concern over the gradual disappearance of onthel bicycles amidst the wave of modernization in the city of Bandung. This project aimed to document the scriptwriting process of a documentary film by applying an expository narrative approach, in which the writer served as the scriptwriter. The film was developed through three main stages: pre- production, production, and post-production. During the pre-production phase, the writer conducted in-depth research and field observations, and developed a script framework, synopsis, treatment, and interview questions. The production phase involved filming, conducting interviews, and recording voice-over narration. Post- production included visual and audio editing as well as finalizing the distribution through the YouTube platform. The final result was a documentary that not only delivered historical information but also raised emotional awareness about the importance of preserving traditional values. In conclusion, the application of an expository narrative successfully strengthened the storytelling structure and provided a deeper understanding of the vintage bicycle community in Bandung.